Pendampingan Pengajuan Perizinan Pengurusan Sertifikasi Halal Sebagai Legalitas Produk UMKM Emiro - Viga Esa Rizkhie; Eka Farida (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
ABSTRACT Product assistance program for micro, small and medium enterprises (MSMEs). Management Halal Certificate through “SEHATI” program carried out through outreach activities and programs assistance in processing halal certification as an effort to increase consumer confidence in market share, because the products being marketed are legal smart and competent. Apart from that, with the government's